Pengaruh Corporate Social Responsibility, Profitabilitas, Dan Leverage Terhadap Kinerja Keuangan (Studi Pada Perusahaan Property dan Real Estate Yang terdaftar Di Bursa Efek Indonesia Tahun 2017-2018) - Jumani Jumani; Afi Racmat Slamet; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of Corporate Social Responsibility, Profitability proxied by Return On Assets (ROA), and Leverage proxied by Debt To Asset Ratio (DAR) and Debt To Equity Ratio (DER) on financial performance which is proxied by Net Profit Margin (NPM) and Return On Sales (ROS) in Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) in 2017-2018. The population in this study amounted to 48 Property and Real Estate companies listed on the Indonesia Stock Exchange. The technique used in this research is purposive sampling with criteria. Obtained a sample of 35 companies. The analysis technique used is multiple linear regression, the classic assumption test, and hypothesis testing using the t test for partial and F tests for simultaneous testing. The results of this study indicate that partially the influence of CSR on financial performance that is proxied by NPM does not have a significant effect but partially significant effect on ROS. Profitability that is proxied by ROA partially has a significant effect on financial performance that is proxied by NPM but does not significantly influence ROS. Leverage proxied by DAR has a significant effect on financial performance proxied by NPM but does not significantly influence ROS, whereas partially DER has no significant effect on financial performance proxied by NPM and ROS. Simultaneously CSR, ROA, DAR, DER significantly influence financial performance which is proxied by NPM and ROS.Keywords: Corporate Social Responsibility, Profitability, Leverage, Return On Sales.